1993
DOI: 10.1046/j.1468-2982.1993.1301037.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Increased Amplitude of Contingent Negative Variation in Migraine Due to Cortical Hyperactivity or to Reduced Habituation?

Abstract: The aim of this study was to compare the habituation kinetics of contingent negative variation (CNV) between 12 migraineurs without aura and matched healthy controls. CNV was studied with a 3 sec interval between the warning stimulus (WS) and the imperative stimulus (IS). The data from (a) the total interval (WS-IS), (b) early component, and (c) late component were analyzed. During successive trials the habituation kinetics were determined using regression analysis. On CNV averaged over 32 trials, migraine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
105
2
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 7 publications
10
105
2
1
Order By: Relevance
“…We manipulated sensory anticipation within a CNV paradigm by inserting all task-relevant response information either at the instant of the warning stimulus or at the instant of the response stimulus. In correspondence with our findings during a classic CNV paradigm in a forewarned simple reaction time task~Mulder et al, 2001!, we did not find any evidence for the larger interictal CNV early and late wave amplitudes that are often reported for migraineurs without aura~e.g., Böcker et al, 1990;Kropp & Gerber, 1993a, 1993b In fact, we even found a smaller CNV late wave in migraineurs without aura than in healthy matched controls. This disparity with other studies could be due to our relatively young, homogenous, nonclinic sample of migraineurs having a relatively short migraine history compared to studies reporting large CNV amplitudes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We manipulated sensory anticipation within a CNV paradigm by inserting all task-relevant response information either at the instant of the warning stimulus or at the instant of the response stimulus. In correspondence with our findings during a classic CNV paradigm in a forewarned simple reaction time task~Mulder et al, 2001!, we did not find any evidence for the larger interictal CNV early and late wave amplitudes that are often reported for migraineurs without aura~e.g., Böcker et al, 1990;Kropp & Gerber, 1993a, 1993b In fact, we even found a smaller CNV late wave in migraineurs without aura than in healthy matched controls. This disparity with other studies could be due to our relatively young, homogenous, nonclinic sample of migraineurs having a relatively short migraine history compared to studies reporting large CNV amplitudes.…”
Section: Discussionmentioning
confidence: 51%
“…is recorded during the foreperiod bridging a warning stimulus and an imperative stimulus, and comprises an early and a late component that become clearly visible if the foreperiod is longer than 2 s~e.g., Loveless & Sanford, 1974!. Various studies have demonstrated a larger, that is, more negative, CNV amplitude in migraine patients during short foreperiods Böcker, Timsit-Berthier, Schoenen, & Brunia, 1990;Maertens de Noordhout, Timsit-Berthier, Timsit, & Schoenen, 1987;!. Studies employing longer foreperiods predominantly report a larger early wave amplitude in migraine without aura~Böcker et al, 1990; Kropp & Gerber, 1993a;1993b; larger late wave amplitudes have also been reported~Böcker et al, 1990!. These augmented CNV amplitudes are believed to be a manifestation of cortical hyperexcitability, induced by hyperactive central catecholaminergic systems~Libet, 1979; Maertens de Noordhout et al, 1987;Nagel-Leiby, Welch, D'Andrea, Grunfeld, & Brown, 1990;Schoenen et al, 1986;Timsit-Berthier, Mantanus, Poncelet, Marissiaux, & Legros, 1986;Timsit-Berthier, Mantanus, Poncelet, et al, 1986!. In addition, the CNV appears to be sensitive to the temporal proximity of a migraine attack.…”
mentioning
confidence: 99%
“…CDH patients evolved from migraine showed a reduced negativity of the late component and a pronounced PINV compared to migraineurs and healthy subjects, while both patient groups showed reduced habituation of the early CNV component. The former abnormality, observed in major depression and anxiety disorders, may be due to the worsening of disease while the latter feature, independently from the clinical course of disease, may be a basic characteristic of migraine brain [37]. The authors concluded that CNV features may be predictive of transformed migraine.…”
Section: Event-related Potentialsmentioning
confidence: 97%
“…They might favor the hypothesis [48] that visual dysfunctions in migraine with aura are secondary to a loss of inhibitory GABAergic interneurons in the visual cortex due to repeated parenchymal insults during the aura, although these abnormalities were not more pronounced in patients with more frequent attacks or longer disease duration. [62,63]. High VEP and CNV amplitudes decreased after prophylactic treatment with a betablocker [6,62].…”
Section: Psychophysical Studies Of the Visual Pathwaysmentioning
confidence: 99%